Students’ Perceptions about Offline Vs Online Learning System in English Subject of the Twelfth Grade at SMAN 1 Pahae Julu North Sumatera Province - Clarisa N. R Simamora; Yuli Tiarina (Journal of English Language Teaching, 2023)
While there is a lot of research that focuses on discovering students' perceptions of online learning, studies on perceptions of online vs. offline is generally ignored. Therefore, this study tries to fill this void. The main objective of this study was to determine students' perceptions of offline vs. online. In this study, researcher used a quantitative descriptive method. 142 students were selected as participants for this study. They were students of class XII IPA and XII IPS SMAN 1 Pahae Julu. In collecting data, the researcher used a questionnaire with a Likert scale and the researcher distributed the questionnaire directly to each participant class. The results of the study found that students showed a very positive perception towards offline learning which can be seen from the average score on each indicator. These findings then showed that students prefer offline learning than online learning so that offline learning is more recommended for use when teaching.